An allostatic epigenetic memory on chromatin footprints after double-hit acute stress - Salvatore G. Caradonna; Matthew R. Paul; Jordan Marrocco (Neurobiology of Stress, 2022)
Stress induces allostatic responses, whose limits depend on genetic background and the nature of the challenges. Allostatic load reflects the cumulation of these reponses over the course of life. Acute stress is usually associated with adaptive responses, although, depending on the intensity of the stress and individual differences , some may experience maladaptive coping that persists through life and may influence subsequent responses to stressful events, as is the case of post-traumatic stress disorder. We investigated the behavioral traits and epigenetic signatures in a double-hit mouse model of acute stress in which heterotypic stressors (acute swim stress and acute restraint stress) were applied within a 7-day interval period. The ventral hippocampus was isolated to study the footprints of chromatin accessibility driven by exposure to double-hit stress. Using ATAC sequencing to determine regions of open chromatin, we showed that depending on the number of acute stressors, several gene sets related to development, immune function, cell starvation, translation, the cytoskeleton, and DNA modification were reprogrammed in both males and females. Chromatin accessibility for transcription factor binding sites showed that stress altered the accessibility for androgen, glucocorticoid, and mineralocorticoid receptor binding sites (AREs/GREs) at the genome-wide level, with double-hit stressed mice displaying a profile unique from either single hit of acute stress. The investigation of AREs/GREs adjacent to gene coding regions revealed several stress-related genes, including Fkbp5, Zbtb16, and Ddc, whose chromatin accessibility was affected by prior exposure to stress. These data demonstrate that acute stress is not truly acute because it induces allostatic signatures that persist in the epigenome and may manifest when a second challenge hits later in life.